Somatic voices in performance research and beyond - Kapadocha, Christina, 1983- (Routledge, 2022)
"Somatic Voices in Performance Research and Beyond brings together a community of international practitioner-researchers who explore voice through soma or soma through voice. Somatic methodologies offer research processes within a new area of vocal, somatic and performance praxis. Voicework and theoretical ideas emerge from dance, acting and performance training while they also move beyond commonly recognized somatics and performance processes. From philosophies and pedagogies to ethnic-racial and queer studies, this collection advances embodied aspects of voices, the multidisciplinary potentialities of somatic studies, vocal diversity and inclusion, somatic modes of sounding, listening and writing voice. Methodologies that can be found in this collection draw on: Eastern traditions Body psychotherapy-somatic psychology Alexander Technique, Feldenkrais Method Authentic Movement, Body-Mind Centering, Continuum Movement, Integrative Bodywork and Movement Therapy Fitzmaurice Voicework, Linklater Technique, Roy Hart Method Post-Stanislavski and post-Grotowski actor-training traditions Somaesthetics The volume also includes contributions by the founders of: Shin somatics, Body and Earth, Voice Movement Integration SOMart, Somatic Acting Process This book is a polyphonic and multimodal compilation of experiential invitations to each reader's own somatic voice. It culminates with the "voices" of contributing participants to a praxical symposium at East 15 Acting School in London (19-20 July 2019). It fills a significant gap for scholars in the field of voice studies, theatre studies, somatic studies, artistic research and pedagogy. It is also a vital read for graduate students, doctoral and postdoctoral researchers"--